2018
DOI: 10.1590/1983-40632018v4850404
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress and physiological changes in watermelon seeds

Abstract: Given that watermelon is a crop widespread around the world, there is considerable interest in verifying how its seeds physiologically behave under unfavorable temperature conditions. This study aimed to evaluate the biochemical changes mobilization and reserves degradation, as well as the enzyme activity, during seed germination and initial growth of watermelon seedlings subjected to thermal stress, using temperature, germination percentage, germination rate and relative germination frequency over the incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The negative effects of high temperatures during germination were also observed for carrot (Pereira et al 2007) and pepper (Diel et al 2019) cultivars, which showed a lower germination rate Heat stress mitigation on the germination and initial development of carrot seedlings using plant growth regulators when subjected to temperatures above standard ones for the species. In watermelon seeds, the temperature of 30 ºC caused a reduction of 80 % in germination (Silva et al 2018).…”
Section: Source Of Variationmentioning
confidence: 99%
“…The negative effects of high temperatures during germination were also observed for carrot (Pereira et al 2007) and pepper (Diel et al 2019) cultivars, which showed a lower germination rate Heat stress mitigation on the germination and initial development of carrot seedlings using plant growth regulators when subjected to temperatures above standard ones for the species. In watermelon seeds, the temperature of 30 ºC caused a reduction of 80 % in germination (Silva et al 2018).…”
Section: Source Of Variationmentioning
confidence: 99%
“…Changes and responses to thermal stress induced in the plant occur at all functional levels of the organism, which are reversible at first, but may become permanent. Even if the stress condition is temporary, the plant vitality decreases according to the stress duration (Silva et al, 2018). Understanding the response of plants to high temperatures and the adaptation mechanisms they developed is important to maintain agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nas sementes, a temperatura atua tanto na indução e quebra de dormência quanto no crescimento embrionário (SILVA et al, 2018). Cada espécie de semente possui uma faixa de temperatura ideal para ocorrer a germinação e emergência, e à medida que a temperatura aumenta acima do valor ótimo, a germinação fica mais lenta e as sementes menos vigorosas, não resistindo ao estresse imposto pelo ambiente (MELO et al, 2012).…”
Section: Introductionunclassified